Cervicovaginal mucus barrier properties during pregnancy are impacted by the vaginal microbiome - Zierden, Hannah C.; DeLong, Kevin; Zulfiqar, Fareeha; Ortiz, Jairo Ortiz; Laney, Victoria; Bensouda, Sabrine; Hernández, Nicole; Hoang, Thuy M.; Lai, Samuel K.; Hanes, Justin; Burke, Anne E.; Ensign, Laura M. (Frontiers in Cellular and Infection Microbiology, 2023)
Mucus in the female reproductive tract acts as a barrier that traps and eliminates pathogens and foreign particles via steric and adhesive interactions. During pregnancy, mucus protects the uterine environment from ascension of pathogens and bacteria from the vagina into the uterus, a potential contributor to intrauterine inflammation and preterm birth. As recent work has demonstrated the benefit of vaginal drug delivery in treating women’s health indications, we sought to define the barrier properties of human cervicovaginal mucus (CVM) during pregnancy to inform the design of vaginally delivered therapeutics during pregnancy. CVM samples were self-collected by pregnant participants over the course of pregnancy, and barrier properties were quantified using multiple particle tracking. Further, we observed that vaginal microbiota is most predictive of CVM barrier properties and of timing of parturition. This knowledge informs our understanding of how infections occur during pregnancy, and directs the engineering of targeted drug treatments for indications during pregnancy.